Localization of a Cardiolipin Synthase in Helicobacter pylori and Its Impact on the Flagellar Sheath Proteome - Doreen Nguyen; Nathan East; Vincent J. Starai; Timothy R. Hoover (Microbiology Research)
Helicobacter pylori, which colonizes the human gastric mucosa, uses a cluster of polar, sheathed flagella to swim across the mucous layer of the stomach. The function and biogenesis of the H. pylori flagellar sheath are poorly understood. Cardiolipin is a phospholipid that accumulates in regions of the membrane that have negative curvature, such as the cell pole, cell septum, and flagellar sheath. The final step in cardiolipin biosynthesis is catalyzed by cardiolipin synthase. H. pylori has at least two cardiolipin synthases, one of which is cardiolipin synthase C (ClsC). Bioinformatic analysis revealed that homologs of H. pylori ClsC are restricted to Helicobacter species that have sheathed flagella and the ClsC homologs are predicted lipoproteins. Fluorescence microscopy revealed that a ClsC super-folder green fluorescent protein localized to the cell pole and cell septum in H. pylori G27. Comparing the proteomes of isolated sheathed flagella from the H. pylori B128 wild type and a clsC::cat mutant, we identified five proteins that were absent in the mutant flagellum preparations. One of the proteins was FaaA, an autotransporter that localizes to the flagellar sheath. These findings suggest that the localization of FaaA and possibly other proteins to the flagellar sheath is dependent on ClsC.